2018
DOI: 10.1021/acsearthspacechem.8b00143
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Dissolution Rates at Crystal Surfaces Using 3D X-ray Microtomography

Abstract: Investigations of mineral surface reactivity have recently challenged the classical approach of determining dissolution rates from mineral powders as crystals often exhibit heterogeneous and/or anisotropic reactivity. However, face-specific measurements are restricted to small areas at the surface and limited depth and ignore the contribution of the crystal edges to the whole process. Here, we provide a detailed characterization of the dissolution kinetics at pH 4.0 of a single calcite crystal in 3D using X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 63 publications
(116 reference statements)
9
63
0
Order By: Relevance
“…The average of all the calcite cement rates, excluding the time lapses the samples were influenced by polishing, is 0.6 ± 0. Such as in 3D studies (e.g., [19]), we show that VSI data also permits the study of different crystal faces, edges and corners and provide total material fluxes in the units mol•s −1 . This 3D study [19], reported three orders of magnitude higher calcite dissolution rates (total rates) than what we measured here, but the authors used an acidic solution (pH = 4) for the experiments, much lower than one used here (pH = 8.7).…”
Section: Relevance To Previous Research and Implicationssupporting
confidence: 60%
See 2 more Smart Citations
“…The average of all the calcite cement rates, excluding the time lapses the samples were influenced by polishing, is 0.6 ± 0. Such as in 3D studies (e.g., [19]), we show that VSI data also permits the study of different crystal faces, edges and corners and provide total material fluxes in the units mol•s −1 . This 3D study [19], reported three orders of magnitude higher calcite dissolution rates (total rates) than what we measured here, but the authors used an acidic solution (pH = 4) for the experiments, much lower than one used here (pH = 8.7).…”
Section: Relevance To Previous Research and Implicationssupporting
confidence: 60%
“…Such as in 3D studies (e.g., [19]), we show that VSI data also permits the study of different crystal faces, edges and corners and provide total material fluxes in the units mol•s −1 . This 3D study [19], reported three orders of magnitude higher calcite dissolution rates (total rates) than what we measured here, but the authors used an acidic solution (pH = 4) for the experiments, much lower than one used here (pH = 8.7). As reported before [12], due to the uncertainty related in defining "reactive surface area", the highest differences in rate magnitude are found in studies that measured rates from fluid chemistry.…”
Section: Relevance To Previous Research and Implicationssupporting
confidence: 60%
See 1 more Smart Citation
“…The transformation was applied to the other VOIs, so that the topography evolution of the surface extracts is directly comparable. This technique is preferred over the extraction of the VOIs from the segmented images, the direct registration of which, in a horizontal plane, would highlight interpolation steps at the crystal surface, which can be confused with crystal surface steps (see for instance Figure 2 shown in Noiriel et al, 2019). After segmentation of the grayscale VOIs using the same procedure as described above (see section 2.3.1), the topography of the fluid-solid interface was extracted.…”
Section: Examination Of Surface Topography Evolutionmentioning
confidence: 99%
“…Although it has long been assumed that crystal edges provide a source of reactive sites (Schott et al, 1989), it is only very recently than the quantitative contribution of crystal edges to dissolution rates has been evaluated experimentally (Noiriel et al, 2019), using X-ray microtomography imaging (XMT). By enabling true 3D space, XMT should permit a significant extension to current methods and models by singling out the reactivity of crystal corners and edges, and to fill the gap between fine-scale (nm-to µm-scale) measurements of surface reactivity and macroscopic determination of bulk rates on powders.…”
Section: Introductionmentioning
confidence: 99%